Comparison of Active And Passive Investment Strategies on The Indonesian Stock Exchange 2013 -2024 With The Magic Formula Method - Rinaldo Adi Sarosa; Putu Anom Mahadwartha (Green Publisher Indonesia, 2024)
This research aims to compare Active and Passive Investment Strategies on the Indonesian Stock Exchange for the 2013-2024 Using the Magic Formula Method introduced by Joel Greenblatt (2010), which is then optimized again using the Single Index Model. Magic formula is a simple stock selection strategy by sorting stocks based on Return on Capital (ROC) and Earning Yield (EY). The shares to be selected are included in the Kompas100 Index. The selected shares have also been listed on the stock exchange for a minimum of 18 months. Shares included in financial shares will be eliminated. The next step is to select 20 shares to be formed into a Portfolio based on the top ranking of the ROC and EY scores, these 20 shares will be optimized using the Single Index Model method. For active strategies, rebalancing will be carried out every year, while for passive strategies, buy and hold will be carried out. The results of this active strategy will be compared with passive strategies and IHSG. Portfolio measurement will be carried out in 4 ways, namely: return, Sharpe ratio, Treynor ratio and Jensen Alpha. The return from the optimized Magic Formula shows a value of 217.04%, higher than the original Magic Formula return of 43.43% and the passive strategy of 35.04% and the IHSG return of 47%, but the final research results of the portfolio show measurements based on return, ratio Sharpe, and Treynor ratios were not significantly different, being significantly different only from Jensen Alpha measurements.